LITHIUM ISOTOPIC SYSTEMATICS OF THE MANTLE-DERIVED ULTRAMAFIC XENOLITHS: IMPLICATIONS FOR EM1 ORIGIN - Nishio Y.; Nakai S.; Yamamoto J.; Sumino H.; Matsumoto T.; Prikhod'ko V.S.; Arai S. (My University, 2004)
Isotopic signatures of mantle-derived xenoliths have provided much information on the evolution of their mantle source regions. A recently developed multiple-collector inductively coupled plasma mass spectrometry method allows precise and accurate lithium isotopic determinations of Li-poor samples such as peridotites. We present Li–Sr–Nd isotopic systematics of clinopyroxenes (CPXs) in mantle-derived ultramafic xenoliths. The results show that Ichino-megata (Northeastern Japan) and Bullenmerri (Southeastern Australia) samples have positive δ7Li values (δ7Li∼+4 to +7‰, δ7Li=[[7Li/6Li]sample/[7Li/6Li]L-SVEC standard−1]×1000) common to values previously reported for terrestrial volcanic rocks. By contrast, unusually low δ7Li values (δ7Li∼−17‰) are observed in many samples from the Far East region of Russia (Sveyagin, Ennokentiev, and Fevralsky) and southwestern Japan (Kurose and Takashima). The δ7Li values of Sikhote-Alin (Sveyagin and Ennokentiev) samples vary widely from −17.1‰ to −3.1‰, while the δ7Li values are positively correlated with 143Nd/144Nd, and negatively correlated with 87Sr/86Sr. On the other hand, the δ7Li values of the Bullenmerri samples are essentially constant (δ7Li=+5.0 to +6.0‰), while the 87Sr/86Sr (0.7027∼0.7098) and 143Nd/144Nd ratios (0.51224∼0.51297) vary widely. These features can be explained by the results of a binary mixing between a depleted component (low-87Sr/86Sr, and high-143Nd/144Nd) and an enriched component (high-87Sr/86Sr, and low-143Nd/144Nd). The enriched component (metasomatic agent) in the mantle beneath the Sikhote-Alin area has extraordinarily low δ7Li value (<−17‰), whereas the metasomatic agent in the mantle beneath the Bullenmerri area has positive δ7Li value (+6‰). Based on the Sr–Nd isotopic systematics and coexistent hydrous mineral, metasomatic agents of the Sikhote-Alin and Bullenmerri samples are classified into anhydrous EM1-type and hydrous EM2-type, respectively. From these features, we infer that anhydrous EM1-like metasomatic agent may have an extremely low δ7Li value, whereas hydrous EM2-like metasomatic agent may have a positive δ7Li value. It has been predicted that the δ7Li value of subducted highly altered mid-ocean ridge basalt (MORB) would be extremely low compared to that of fresh MORB due to the preferential loss of heavier Li (δ7Li>altered MORB) from the subducted slab during dehydration at low temperature. Consequently, it is deduced that Li of metasomatic agent with an extremely low δ7Li value is derived from subducted highly altered basalt. The enrichment of isotopically light Li (low δ7Li) may be a general property of EM1 mantle reservoir. The Li isotopic data suggest further that the EM1 and HIMU sources originate from different parts of a recycling oceanic crust. This is essentially the same as the models proposed previously based on the radiogenic isotopic data, but with the Li isotopic data requiring uppermost, highly altered basaltic crust as well as pelagic sediment in the EM1 source, but not so in the HIMU end-member. Because of the apparent sensitivity of Li isotopic composition to the alteration profile of subducted MORB, it may provide complementary information to Sr, Nd, and Pb isotopic compositions regarding the mantle source.